Impact of the disclosure of amyloid‐PET results to patients with subjective cognitive decline: the AMYPAD Diagnostic and Patient Management Study (DPMS): Neuroimaging / Normal brain aging. (7th December 2020) - Poitrine, Léa; Altomare, Daniele; Moro, Christian; Collij, Lyduine; Alves, Isadora Lopes; Barkhof, Frederik; Saint‐Aubert, Laure; Delrieu, Julien; Jessen, Frank; Félez‐Sánchez, Marta; Lee, Lean; Walker, Zuzana; et al.
Abstract: Background: Amyloid‐PET is increasingly used for diagnostic purposes in patients with cognitive impairment due to suspected Alzheimer's disease. However, cognitively unimpaired individuals are frequently included in research studies involving amyloid‐PET scan. Even if amyloid‐PET is not clinically recommended in these cases, these patients often want to know their amyloid status, a strong risk factor for incident dementia. Currently, evidence on the impact of the disclosure of amyloid‐PET results on patients' psychological well‐being is scanty. The aim of this sub‐study is to assess how a positive amyloid‐PET result affects the psychological well‐being of patients with subjective cognitive decline plus (SCD+) enrolled in a prospective study on the diagnostic utility of amyloid PET (AMYPAD‐DPMS). Method: The impact of the disclosure of amyloid‐PET results on patient's psychological well‐being was investigated using the Impact of Event Scale–Revised (IES‐R). IES‐R is used to detect potential changes from the current time point and a previous time point preceding up to 7 days an event (the amyloid‐PET result disclosure in this case). IES‐R was administered 1‐3 days post‐disclosure, and consists of one total score (0‐88) and three sub‐scores (0‐4): avoidance (avoidance of thoughts, feelings, memories or situations), intrusions (intrusive memories, thoughts, or feelings causing distress), and hyperarousal (hypervigilance, feeling watchful and on guard, difficulty concentrating). IES‐R total score between 12‐32: symptoms of post‐traumatic stress, patient monitoring is required; ≥33: probable presence of a post‐traumatic stress disorder. Result: So far, 36 SCD+ participants of AMYPAD‐DPMS, who received their amyloid‐PET results, have accepted to participate in this sub‐study. Amyloid‐positive patients (n=9) had higher IES‐R total score (median=10, lower‐upper quartiles=1‐14) than amyloid‐negatives (1, 0‐6), albeit at trend level ( p =0.052). We also observed higher avoidance scores in amyloid‐positives compared to amyloid‐negatives (0, 0.00‐0.62 vs. 0, 0.00‐0.00, p =0.004), but no differences in the other two sub‐scores ( p >0.05). Conclusion: These preliminary data on 36 participants suggests that the disclosure of positive amyloid scan to an SCD+ patient is associated with the avoidance of thoughts and memories of the news. Future analyses will address additional outcome measures (e.g. post‐disclosure anxiety and depression) and factors associated with a milder psychological impact in amyloid‐positive patients.